2017
DOI: 10.1002/pi.5397
|View full text |Cite
|
Sign up to set email alerts
|

Molecular design of interfacial layers based on conjugated polythiophenes for polymer and hybrid solar cells

Abstract: In the past two decades, bulk heterojunction organic photovoltaic (OPV) devices have emerged as attractive candidates for solar energy conversion due to their lightweight design and potential for low‐cost, high‐throughput, solution‐phase processability. Interfacial engineering is a proven efficient approach to achieve OPV devices with high power conversion efficiencies. This mini‐review provides an overview of the key structural considerations necessary when undertaking the molecular design of conjugated polye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 18 publications
(38 citation statements)
references
References 129 publications
(262 reference statements)
1
37
0
Order By: Relevance
“…[4][5][6][7][8] Even though most research activities have been oriented on the development of novel active layer materials with appropriate optoelectronic properties, the introduction of interlayer materials has become a widely accepted approach to further enhance the device efficiency. [9][10][11][12][13][14][15][16][17] One class of interlayer materials of particular interest are conjugated polyelectrolytes (CPEs). They can be processed from eco-friendly, orthogonal solvents, thereby preventing re-dissolution of the underlying layer during device fabrication.…”
Section: Abstract: Conjugated Polyelectrolytes; Polymer Solar Cells; mentioning
confidence: 99%
See 1 more Smart Citation
“…[4][5][6][7][8] Even though most research activities have been oriented on the development of novel active layer materials with appropriate optoelectronic properties, the introduction of interlayer materials has become a widely accepted approach to further enhance the device efficiency. [9][10][11][12][13][14][15][16][17] One class of interlayer materials of particular interest are conjugated polyelectrolytes (CPEs). They can be processed from eco-friendly, orthogonal solvents, thereby preventing re-dissolution of the underlying layer during device fabrication.…”
Section: Abstract: Conjugated Polyelectrolytes; Polymer Solar Cells; mentioning
confidence: 99%
“…The conjugated polymer backbone has not been explored much further than polyfluorene and polythiophene derivatives and most variation has been introduced in the ionic moieties. 12 Previous work in our group focused on imidazolium-functionalized polythiophenes, outperforming the ammonium-functionalized counterparts. 11 More recently, impedance spectroscopy measurements revealed that the dielectric permittivity, induced by the ionic functionalities, is an important parameter to improve charge collection.…”
Section: Abstract: Conjugated Polyelectrolytes; Polymer Solar Cells; mentioning
confidence: 99%
“…In all, 143 new P3HTV derivatives were obtained. We choose to substitute at position 4 of the thiophene ring because there have already been reports in the literature of substitutions at this position for similar materials, such as P3HT , , , . As regards the vinyl group, only one chemical substitution was performed in the position highlighted in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…We choose to substitute at position 4 of the thiophene ring because there have already been reports in the literature of substitutions at this position for similar materials, such as P3HT. 9,13,14,21 As regards the vinyl group, only one chemical substitution was performed in the position highlighted in Fig. 1 because there are works in the literature that indicate that replacing the two hydrogens of the vinyl group causes a considerable worsening in the morphology of the material without significant gains in electronic structure.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation